The Impact of Gadget Use on Elementary School Students' Interest in Learning - Kurnia Ilahi, Hiru; Putri Rahma Ilahi, Salsabila; Adrias, Adrias; Wahyudi, Hendra; Suciana, Fadila (International Journal of Elementary School, 2025)
To facilitate the educational process, the presence of educational institutions is essential. Elementary school serves as a foundation where students acquire knowledge and education. At this stage, the surrounding environment plays a significant role in shaping development and fostering curiosity. Gadgets attract elementary school students because of their diverse features. However, excessive use may reduce students’ interest in learning, as they often spend more time playing games, watching movies, or browsing unproductive social media content. A lack of parental attention further aggravates this issue, leading to decreased learning motivation and increased passivity. This study aims to examine the impact of gadget use on elementary school students’ interest in learning. It employs a qualitative approach with content analysis to review and interpret relevant studies. The findings suggest that gadgets can provide positive contributions when used wisely under the supervision of teachers and parents. Conversely, without proper guidance, gadget use may have negative implications, including reduced learning interest and a decline in moral values.